Relationship between moderate-to-vigorous physical activity, abdominal fat and immunometabolic markers in postmenopausal women. (November 2015) - Diniz, T.A.; Fortaleza, A.C.S.; Buonani, C.; Rossi, F.E.; Neves, L.M.; Lira, F.S.; Freitas-Junior, I.F.
Abstract: Objects: To assess the burden of levels of physical activity, non-esterified fatty acids (NEFA), triacylglycerol and abdominal fat on the immunometabolic profile of postmenopausal women. Study design: Forty-nine postmenopausal women [mean age 59.43 (standard deviation 5.61) years] who did not undertake regular physical exercise participated in this study. Body composition was assessed using dual-energy X-ray absorptiometry, and levels of NEFA, tumour necrosis factor-α, adiponectin, insulin and triacylglycerol were assessed using fasting blood samples. The level of physical activity was assessed using an accelerometer (Actigraph GTX3x), and reported as counts/min, time spent undertaking sedentary activities and time spent undertaking moderate-to-vigorous physical activity (MVPA). The following conditions were considered to be risk factors: (i) sedentary lifestyle (<150 min of MVPA per week); (ii) high level (above median) of abdominal fat; and (iii) hypertriacylglycerolaemia (<150 mg/dl of triacylglycerol). Results: In comparison with active women, sedentary women had higher levels of body fat (%) ( p = 0.041) and NEFA ( p = 0.064). Women with higher levels of abdominal fat had impaired insulin resistance (HOMA-IR) ( p = 0.016) and spent more time undertaking sedentary activities ( p = 0.043). Moreover, the women with two risk factors or more had high levels of NEFA and HOMA-IR ( p < 0.05), as well as an eight-fold higher risk of a high level of NEFA, independent of age ( p < 0.05). No significant relationship was found between levels of physical activity, abdominal fat, tumour necrosis factor-α and adiponectin ( p > 0.05). Conclusion: Postmenopausal women with a combination of hypertriacylglycerolaemia, a high level of abdominal fat and a sedentary lifestyle are more likely to have metabolic disturbances.